Sleep spindle characteristics in adolescents. Issue 6 (June 2019) - Goldstone, Aimée; Willoughby, Adrian R.; de Zambotti, Massimiliano; Clark, Duncan B.; Sullivan, Edith V.; Hasler, Brant P.; Franzen, Peter L.; Prouty, Devin E.; Colrain, Ian M.; Baker, Fiona C.
Highlights: Younger adolescents exhibit fewer fast spindles compared to older adolescents. Sleep spindles may serve as a marker of adolescent brain development. Sleep spindle changes during adolescence are not fully characterized by sigma power. Abstract: Objective: Sleep changes substantially during adolescence; however, our understanding of age-related differences in specific electroencephalographic waveforms during this developmental period is limited. Method: Sigma power, spindle characteristics and cognitive data were calculated for fast (∼13 Hz) central and slow (∼11 Hz) frontal sleep spindles for a large cross-sectional sample of adolescents (N = 134, aged 12–21 years, from the National Consortium on Alcohol and NeuroDevelopment in Adolescence (NCANDA) study). Results: Older age (and advanced pubertal development) was associated with lower absolute sigma power and greater fast spindle density, with spindles having a shorter duration and smaller amplitude and occurring at a faster average frequency than at a younger age. Spindle characteristics were not directly associated with cognition. An indirect relationship (age * density) provided some evidence for an association between better episodic memory performance and greater spindle density only for younger adolescents. Conclusion: Spindle characteristics in adolescents differed according to age, possibly reflecting underlying differences in thalamo-cortical connectivity, and may play a role in episodic memory early in adolescence. Significance: Sleep spindles may serve as a marker of adolescent development, likely reflecting brain maturational status. Investigating specific spindle characteristics, in addition to sigma power, is necessary to fully characterize spindles during adolescence.